Reprogramming of human induced pluripotent stem cells and growth performance in 3D peptide hydrogel matrix system and potential applications - Cui, Muyun (Kansas State University, 2024)
Human-induced pluripotent stem cells (hiPSCs) represent invaluable tools in biomedical research due to their exceptional versatility. This study delves into the intricate realm of hiPSC culture maintenance and application within three-dimensional (3D) systems, aiming to unravel how distinct culture conditions intricately shape cellular behavior. The investigation into hiPSC applications uncovers three notable advantages. First, it demonstrates the superior functional enrichment released from hiPSCs cultured in a 3D environment. Second, it highlights the efficacy of employing a 3D generation system for hiPSC induction from somatic and blood cells. Thirdly, the comprehensive comparison also encompasses mTeSR1 medium and E8 medium across various peptide hydrogel concentrations and configurations, including 3D embedded and 3D suspension peptide hydrogel matrix. These findings have significant implications for advancing the field of hiPSC cell research and its diverse applications in biomedical science. In particular, when scrutinizing the conventional 2D iPSC generation system against the innovative 3D PGmatrix system, revealed significantly superior performance in hiPSC reprogramming. Importantly, the findings highlight the high efficiency of hiPSC cell harvesting, alongside the reduced time and energy requirements of the 3D hiPSC generation system compared to traditional 2D approaches. Additionally, we demonstrate that culture conditions adaptable for cell growth can be accommodated within the 3D system while maintaining high cell proliferation, viability, and pluripotent gene expression. In summary, this research significantly advances our comprehension of how hiPSCs respond to the intricate milieu of 3D culture conditions, holding the potential to optimize hiPSC applications in various facets of biomedical research, and ultimately propelling advancements in regenerative medicine, disease modeling, and drug development.
Keywords: 3D culture; Cell reprogramming; Human induced pluripotent stem cell; Peptide hydrogel; Extracellular vesicle